Iconographie grecque / par E.Q. Visconti ... - Visconti, Ennio Quirino, 1751-1818. (Tufts University. Tisch Library., 2018)
1 online resource (3 volumes) : illustrations.; The 2 parts of 2d v. have half-title only: Iconographie greque.; Volume 1 of 3.